International Workshop on Documentation and Preservation of Ethiopian Cultural and Art Heritage of the Haddis Alemayehu Cultural and Research Institute, 19 May 2012, Debre Markos University – an Illustrated Conference Report - Ramos, M. (ITYOP?IS – Northeast African Journal of Social Sciences and Humanities (NEAJ), 2016)
The inauguration workshop of the newly founded Haddis Alemayehu Cultural and Research Institute of Debre Markos University was held on 19 May 2012 at Debre Marqos in the historical province of Gojjam. As the University’s Vice President for Academics and Research, the social anthropologist Yilkal Kefale Asres [Yilqal Kefalé Asres], put it: “The workshop included cultural issues such as contributions of oral poetry and other oral literature to the study of culture, the importance and the role of culture in preserving traditional culture in the face of globalization, and the discussion on expectations from our institutions.”